Mindfulness and Symptoms of Depression in Mexican Adolescents High School Students - Veytia-López, Marcela (2016)
The objective of this research was to identify the relation between depressive symptoms and mindfulness levels in mexican adolescents high school students. A cross-sectional survey was conducted with 930 baccalaureate students between 15 and 19 years old was performed. The instruments, CESD (depressive symptoms) and MAAS (mindfulness) were applied, finding a 17.3% prevalence of depressive symptoms, furthermore, 55.2% of participants had low levels of mindfulness, and also adolescents with depressive symptoms have higher levels of mindfulness. The relation between depression symptoms and mindfulness was negative (r= -0.53; <.001). Conclusion: Study the feature of full awareness or mindfulness as a positive psychological factor because it’s reducing effect is demonstrated in psychological symptoms such as depression.